Genesis in late antique poetry - Faulkner, Andrew, 1978-; O'Hogan, Cillian; Wickes, Jeffrey Thomas (CUA studies in early Christianity, 2022)
"The essays in this book study an array of Jewish and Christian responses to the biblical of Genesis as they took shape in specific literary forms-the unique genres of late antique poetry. While late antique and early medieval Jews and Christians did not always agree in their interpretations of Genesis, they participated broadly in a shared culture of poetic production. Though late antique poems developed in a variety of languages and across religious boundaries, scholarly study of late antique poetry has tended to isolate the phenomenon according to language. As a corrective to this linguistic isolation, this book initiates a comparative conversation around the Jewish and Christian poetry that emerged in late antique Aramaic, Greek, Hebrew, Latin, and Syriac. Tending equally to exegetical content and literary form, the essays in this book sit at the intersection of a variety of scholarly conversations-around the history of biblical exegesis, the formation of late antique and early medieval literature and literary culture, and the comparative study of Judaism and Christianity"--